Financial contagion, interest rates and the role of the exchange rate as shock absorber in Central and Eastern Europe - Maurizio Michael Habib (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This paper studies the impact of external factors on daily exchange rates and short-term interest rates in the Czech Republic, Hungary and Poland during the period August 1997 - May 2001.Ind that neither exchange rates nor interest rates are influenced by short-term German interest rates.Nevertheless, 1 show that shocks to emerging-market risk premia had a significant impact on exchange rates in all three Central and Eastern European countries and on interest rates in the Czech Republic.In addition, studying the second moment of the variables, 1 demonstrate that Czech and Polish exchange rates were affected by 'volatility contagion' coming from emerging markets. 1 find also some partial support for the 'volatility contagion' hypothesis on Czech interest rates.These findings shed some doubts on the alleged theoretical ability of a floating exchange rate - such as in the Czech Republic - to absorb external shocks and insulate a country's domestic monetary policy completely.However, the spill-over effect on Czech interest rates might be explained by the 'managed' nature of the exchange rate regime, thereby re-establishing some credibility of the theory.
URN:NBN:fi:bof-201408072043
Keywords: 330; exchange rates; short-term interest rates; volatility; Czech Republic; Hungary; Poland